PELAKSANAAN FUNGSI KELOMPOK KERJA GURU (KKG) DI SEKOLAH DASAR NEGERI (SDN) KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR - Aan Purnanda (Universitas Negeri Padang, 2013)
This research is motivated by not maximal function implementation working group of teachers in Public Elementary School District Sungai Tarab. This study aimed to gain insight into the function. This research is a descriptive study population of all public elementary school teachers in the Sungai Tarab, amounting sample was 223 people with 38 people. Data collection tool was a questionnaire Likert scale models that have been tested for validity and realibilitasnya. The data were processed using the formula mean. The results conclude the general implementation of the function of the working group of teachers in public elementary school in the District of Sungai Tarab is in good category with an average score of 4.33. Thus it can be said that the implementation of the functions of the working group of teachers in public elementary school Sungai Tarab District has done well thus providing benefits in increasing the ability of teachers. Kata Kunci : pelaksanaan fungsi kelompok kerja guru